Loss-of-Learning and the Post-Covid Recovery in Low-Income Countries - Buffie, Edward; Adam, Christopher; Kpodar, Kangni; Zanna, Luis-Felipe. (Washington, D.C. : International Monetary Fund, 2022)
We analyze the medium-term macroeconomic impact of the Covid-19 pandemic and associated lock-down measures on low-income countries. We focus on the impact over the medium-run of the degradation of health and human capital caused by the pandemic and its aftermath, exploring the trade-offs between rebuilding human capital and the recovery of livelihoods and macroeconomic sustainability. A dynamic general equilibrium model is calibrated to reflect the structural characteristics of vulnerable low-income countries and to replicate key dimensions of the Covid-19 shock. We show that absent significant and sustained external financing, the persistence of loss-of-learning effects on labor productivity is likely to make the post-Covid recovery more attenuated and more expensive than many contemporary analyses suggest.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt; Fiscal Policy; International Lending and Debt Problems; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock